2017
DOI: 10.1093/jme/tjx141
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection and Identification of Rickettsia Species in Ticks (Acari: Ixodidae) Collected From Belize, Central America

Abstract: Little is known about tick-borne rickettsial pathogens in Belize, Central America. We tested ixodid ticks for the presence of Rickettsia species in three of the six northern and western Belizean districts. Ticks were collected from domestic animals and tick drags over vegetation in 23 different villages in November 2014, February 2015, and May 2015. A total of 2,506 collected ticks were identified to the following species: Dermacentor nitens Neumann (46.69%), Rhipicephalus sanguineus (Latreille) (19.55%), Rhip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 58 publications
2
24
0
1
Order By: Relevance
“…DNA extraction from ticks were done as described previously [ 18 ]. In brief, individual adult ticks were cut longitudinally into halves using a clean stainless steel No.10 surgical blade (Swan- Morton, Sheffield, United Kingdom).…”
Section: Methodsmentioning
confidence: 99%
“…DNA extraction from ticks were done as described previously [ 18 ]. In brief, individual adult ticks were cut longitudinally into halves using a clean stainless steel No.10 surgical blade (Swan- Morton, Sheffield, United Kingdom).…”
Section: Methodsmentioning
confidence: 99%
“…Another closely related pathogenic species, R. parkeri , was recently reported in Central America, infesting Amblyomma maculatum and Amblyomma ovale (specifically the strain Atlantic rainforest) from Belize. 56 , 57 Although A. maculatum and A. ovale frequently parasitize humans, 47 , 58 until now there are no reports of human infection by these species in the region. Although R. parkeri was isolated in 1939, its involvement as a pathogen for humans was not confirmed until 2004.…”
Section: Rickettsia Species In Ectoparasites In Central Amermentioning
confidence: 99%
“…Multilocus typing showed that 11 of these Rickettsia genotypes can be assigned to two validated Rickettsia species, namely R. amblyommatis (two genotypes) and R. bellii (nine genotypes). These two Rickettsia species are widely present among Central and South American ticks, each infecting more than 10 species 7,[11][12][13][21][22][23][24][25][26] . Their presence in French Guiana was therefore expected, but the observation of novel genotypes indicates the presence of important geographic variability: R. amblyommatis and R. bellii have probably radiated within their respective regions, including French Guiana, into different genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Since none of the 19 Rickettsia genotypes was previously described before this study, no evidence of their pathogenicity currently exists, even for those belonging to validated Rickettsia species. Indeed, although R. amblyommatis and R. bellii are commonly found in the ticks of French Guiana, and more broadly in American ticks 7,[11][12][13][21][22][23][24][25][26] , they have never been found in vertebrate hosts, suggesting that they are nonpathogenicspecies. Interestingly, while the Cayenne tick A. cajennense is one of the most common ticks found in French Guiana, blood-feeding on many different hosts, including humans 8,30,31 , R. amblyommatis (infecting here 25% of the A. cajennense specimens examined) were never detected in humans or animals: while French Guiana is an outermost region of the European Union, with technical and financial resources that close to European countries, no case was notified to date.…”
Section: Discussionmentioning
confidence: 99%